Acceleration of Public Services Through the Program E-Village in Improving Village Government in Pematang Johar Village - Agung Saputra; Khaidir Ali; Siti Hajar (Publik : (Jurnal Ilmu Administrasi), 2021)
Pematang Johar village government is a village that has a lot of potential that can be developed and becomes a program that can improve governance in the village environment. The programs that are carried out in improving the administration of village governance in Pematang Johar Village cannot be separated from the strengthening of village government through programs that serve as an increase in knowledge and skills of human resources, especially in providing optimal services to the community. The program in question is the E-Desa program which aims to provide optimal services to the people of Pematang Johar Village. However, the program still requires steps that can be used by all village communities in obtaining public services in Pematang Johar Village. The purpose of the study was to determine and analyze the acceleration of public services through the E-Desa program in improving village governance in Pematang Johar Village. The method used in this research is qualitative. Strengthening village government in improving public services requires skilled human resources and is able to carry out the steps in implementing the E-Village program. Not only human resources (village government apparatus) must have the skills and knowledge in using the E-Village program through Android phones, but the community must also be able and understand the use of this program.